Penerapan Aromaterapi Lavender terhadap Kualitas Tidur Ibu Postparum Sectio Caesarea di Ruang Gladiol RSUD Dr. Tjitrowardojo Purworejo - Septie Ambarwati; Despita Pramesti (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Background: The impact of pain experienced by post-cesarean section (SC) patients can lead to several specific psychological changes, such as alterations in eating patterns, daily activities, energy levels, and sleep patterns. Individuals who are unwell generally require more sleep than usual; however, in post-surgical patients, sleep disturbances are a common issue. Sleep disorders in post-cesarean patients can be caused by various factors, including pain from the surgical wound, changes in sleep patterns due to caring for a newborn, and stress or anxiety related to childbirth. Objective: To describe the effect of lavender aromatherapy on the sleep quality of post-SC mothers at Tjitrowardojo Regional Hospital, Purworejo. Research Method: This study employed a pre-experimental approach with a one-group pretest-posttest design, aiming to determine changes in sleep quality among post-cesarean section (SC) mothers after the administration of lavender aromatherapy. Sleep quality was measured using the Sleep Quality Scale (SQS), which was administered on the first and third days of the study. Research Results: The administration of lavender aromatherapy successfully improved sleep quality in post-SC patients. Conclusion: Non-pharmacological therapy using lavender aromatherapy can have a positive effect on improving sleep quality in post-SC patients. This is evidenced by the research results showing a decrease in the Sleep Quality Scale (SQS) scores, leading to the conclusion that lavender aromatherapy is effective in enhancing sleep quality in post-operative patients.